Associations of social determinants of health and patient safety in perinatal care: Protocol for a systematic review with meta-analysis - Katharina Averdunk; Céline Miani; Brigitte Strizek; Matthias Weigl (PLoS ONE, 2025)
Background Associations between adverse social conditions and poor health are well documented – also in perinatal care. However, research into the actual ramifications of such disparities for perinatal patient safety remains inconclusive. Therefore, to achieve a comprehensive understanding of the risk and burden of patient harm to disadvantaged people, we aim to systematically review current evidence on social determinants of health (SDoH) and perinatal patient safety. Objective This study protocol outlines definitions, methods, and procedures for a systematic literature review with meta-analysis aiming to synthesise the research base on the associations between SDoH and patient safety in perinatal care. Methods Adhering to PRISMA guidelines, a literature search will be conducted for a systematic review in MEDLINE (PubMed), Scopus database, CINAHL (EBSCO), and Embase (Elsevier) for quantitative studies reporting associations between SDoH and patient safety measures in perinatal care. Data extraction will include study design, population, SDoH variables, outcome measures, effect sizes, and control variables. If deemed feasible after assessment of heterogeneity, narrative synthesis of findings will be complemented by conducting meta-analyses of pooled effect sizes. Methodological quality of included studies will be assessed using JBI Critical Appraisal Tools, and the certainty of evidence using the GRADE tool. This protocol is registered on PROSPERO (CRD420251090149) and OSF ( https://doi.org/10.17605/OSF.IO/UP3JS ). Discussion The review aligns well with current global efforts to promote safe perinatal care and presents an innovative, comprehensive approach for assessing the associations between SDoH and patient safety. The review will provide the first systematic synthesis of current evidence of SDoH and patient safety in perinatal care. Anticipated limitations include heterogeneity of study designs, measures, and outcomes, with expected predominance of observational studies, which may limit causal inferences. However, this review will provide a valuable foundation for further empirical research and interventions to enhance equitable and safe perinatal care.